Communicating computational workflows in a regulatory environment - Keeney, Jonathon G; Gulzar, Naila; Baker, Jack B; Klempir, Ondrej; Hannigan, Geoffrey D; Bitton, Danny A; Maritz, Julia M; King, Charles H S; Patel, Janisha A; Duncan, Paul; Mazumder, Raja (Drug discovery today, 2024)
The volume of nucleic acid sequence data has exploded recently, amplifying the challenge of transforming data into meaningful information. Processing data can require an increasingly complex ecosystem of customized tools, which increases difficulty in communicating analyses in an understandable way yet is of sufficient detail to enable informed decisions or repeats. This can be of particular interest to institutions and companies communicating computations in a regulatory environment. BioCompute Objects (BCOs; an instance of pipeline documentation that conforms to the IEEE 2791-2020 standard) were developed as a standardized mechanism for analysis reporting. A suite of BCOs is presented, representing interconnected elements of a computation modeled after those that might be found in a regulatory submission but are shared publicly - in this case a pipeline designed to identify viral contaminants in biological manufacturing, such as for vaccines.
Keywords: vaccine; vysoce účinné nukleotidové sekvenování; BioCompute; adventitious virus detection; next generation sequencing; metagenomics; Vaccines; vakcíny; Computational Biology; HTS; High-Throughput Nucleotide Sequencing; výpočetní biologie; Workflow; průběh práce